2014
DOI: 10.1021/cg500644w
|View full text |Cite
|
Sign up to set email alerts
|

Probing Crystal Growth of ε- and α-CL-20 Polymorphs via Metastable Phase Transition Using Microscopy and Vibrational Spectroscopy

Abstract: This article presents the evidence of possible route to the formation of ε-and α-polymorphic phases of 2, 4,6,8,10,4,6,8,10, studied through CL-20 solution using reverse and normal precipitation method. Reverse precipitation with instant addition facilitated with the opportunity to track the crystal phases from their immediate formation to end of phase stabilization. Precipitation under apparent conditions to achieve α-or ε-phases, showed initial occurrence of metastable β-phase and subsequent transformation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 41 publications
(83 reference statements)
5
37
0
Order By: Relevance
“…It is well known that CL-20 can be crystallized into four different polymorphs under ambient temperature and pressure conditions, including α-, β-, γ-, and ɛ-, while the hemihydrate α-form is preferentially obtained even small amounts of water present in the reaction medium. [36] However, by adding ɛ-CL-20 and DNDAP to pure water after a few days, we found unexpectedly that some cocrystals precipitated out. To optimize the reaction conditions, three slightly soluble-solvents: H 2 O, H 2 O/methyl acetate, and isopropanol were selected as the reaction medium.…”
Section: Assembly Process Of Cl-20/dndap Cocrystal In Different Solventsmentioning
confidence: 85%
“…It is well known that CL-20 can be crystallized into four different polymorphs under ambient temperature and pressure conditions, including α-, β-, γ-, and ɛ-, while the hemihydrate α-form is preferentially obtained even small amounts of water present in the reaction medium. [36] However, by adding ɛ-CL-20 and DNDAP to pure water after a few days, we found unexpectedly that some cocrystals precipitated out. To optimize the reaction conditions, three slightly soluble-solvents: H 2 O, H 2 O/methyl acetate, and isopropanol were selected as the reaction medium.…”
Section: Assembly Process Of Cl-20/dndap Cocrystal In Different Solventsmentioning
confidence: 85%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 include the a-phase as diamonds, b-phase as needles, and e-phase as bipyramidal crystals [19,20]. Recrystallization of CL-20 matches well with pure a-phase and confirms what has been reported for recrystallized a-CL-20 [18,19]. SEM imaging shows that 1 adopts a unique crystal morphology when compared to the physical mixture of recrystallized components.…”
Section: Characterizationmentioning
confidence: 99%
“…Ghosh et al [19] reported that a-CL-20 was distinguishable in FTIR spectroscopy by the presence of a low intensity hydrate peak at about 3700 cm À1 and a triplet-like feature near 745 cm À1 (739, 750, and 763 cm À1 ). CL-20 recrystallized from DMSO/Water agreed well with the reported spectra and retained a sharp hydrate peak at 3693 cm À1 and a triplet at 739, 750, and 763 cm À1 found in Figure 5.…”
Section: Ftir and Raman Spectroscopymentioning
confidence: 99%
“…Hexanitrohexaazaisowurtzitane (HNIW) is one of the high energy materials (HEMs) that have been developed to obtain an improved performance and low sensitivity. HNIW performs well because it has a higher oxygen balance, density, and detonation velocity than other energetic nitramines such as RDX and HMX . HNIW has five polymorphs because of different molecular structures.…”
Section: Introductionmentioning
confidence: 99%